Genetic and Environmental Factors Affecting TNF-α Responses in Relation to Sudden Infant Death Syndrome - Moscovis, Sophia M.; Gordon, Ann E.; Al Madani, Osama M.; Gleeson, Maree; Scott, Rodney J.; Hall, Sharron T.; Burns, Christine; Blackwell, Caroline (Frontiers in Immunology, 2015)
Dysregulation of inflammatory responses has been suggested to contribute to the events leading to sudden infant deaths.Tumour necrosis factor-α (TNF-α) is a key cytokine in inflammatory responses to infection, and one of its single nucleotide polymorphisms, TNF G-308A, was associated with severe responses to infection. Our objectives were to assess: 1) TNF G-308A in Sudden Infant Death Syndrome (SIDS); 2) in vitro effects of two risk factors for SIDS, virus infection and cigarette smoke on TNF-α responses; 3) effects of gender, TNF G-308A and cigarette smoke on responses to bacterial antigens identified in SIDS infants, lipopolysaccharide (LPS) or toxic shock syndrome toxin (TSST-1). TNF G-308A genotypes were determined by real time PCR for: SIDS infants from Australia, Germany and Hungary; parents of SIDS infants and an unrelated comparison group; populations with reported high (Indigenous Australian), medium (Caucasian) and low (Bangladeshi) incidences of SIDS. The human monocytic cell line THP-1 or peripheral blood monocytic cells (PBMC) from Caucasian donors were stimulated in vitro with LPS or TSST-1. For THP-1 cells and PBMC from blood donors, TNF-α responses to LPS were assessed with surrogates for: virus infection, interferon- (IFN-); cigarette smoke, water-soluble cigarette smoke extract (CSE). For leukocytes from Caucasian donors, TNF-α responses to LPS or TSST-1 were assessed in relation to smoking, genotype and gender. The AA genotype was higher among Australian SIDS infants compared to controls (p=0.03). For THP-1 cells, IFN- enhanced TNF-α elicited by LPS, and CSE alone or in the presence of IFN- reduced the response. For PBMC, there was a similar pattern of effects on TNF-α responses observed with IFN- and CSE. When leukocytes of Caucasian donors were assessed, there were no significant differences in TNF- responses elicited by either LPS or TSST-1 associated with TNF G-308A genotypes assessed in relation to smoking status or gender.